Implementation of collaborative design processes into PLM systems. (13th July 2009) - Pol, Guillaume; Merlo, Christophe; Legardeur, Jeremy; Jared, Graham
Design coordination means project structuring in relation with local objectives identification, resources assignment, task scheduling and performance criteria definition. In small and medium enterprises (SMEs), the design process is generally described at a macro-level which does not fully correspond to the complexity of the real process. A business approach for coordinating design process through the implementation of product life-cycle management (PLM) systems is proposed for improving design coordination in SMEs. Firstly, this business approach is based on a method for analysing informal collaborative practices and modelling detailed design processes. Secondly, these processes are implemented by using PLM technologies. Multi-level workflows are implemented to control progress of design schedule from project management level to document life-cycle management level. Subprocess generation and synchronisation tasks are used to synchronise them from one level to another and 'flexibility nodes' identify choices between different task sequences. An experiment validates the feasibility of this business approach.